Exploring the dynamic and thermo-mechanical behavior of Banana/Kenaf/Jute epoxy hybrid biocomposites: impact of stacking sequences - Sangilimuthukumar Jeyaguru; Senthil Muthu Kumar Thiagamani; Harikrishnan Pulikkalparambil; Suchart Siengchin; Mohamed Hashem; Hassan Fouad (Materials Research Express)
This study investigates the thermal behavior and thermo-mechanical properties of banana, jute, and kenaf fiber-reinforced epoxy composites, focusing on the impact of different layering sequences and hybrid configurations. The novelty of the work lies in the tailored stacking of natural fibers to optimize composite performance, a topic of growing significance in sustainable engineering. Thermal analysis revealed the highest endothermic peak at 72 °C in BJKKJBE hybrid composites, while jute fiber-reinforced composites exhibited a marginally higher peak at 73 °C. Dynamic mechanical analysis highlighted kenaf fiber-reinforced composites as having superior storage modulus values, reaching 152 MPa at 10 Hz, followed by the BJKKJBE hybrid, which achieved 137 MPa. Additionally, banana fiber-reinforced composites and neat epoxy recorded the highest loss modulus values (52 MPa and 51 MPa), indicating excellent energy dissipation. Neat epoxy and kenaf fiber reinforced composites displayed the highest tan delta values, with BJKKJBE hybrids also showing notable damping behavior, suggesting effective vibration attenuation. On the other hand, jute-based composites demonstrated the lowest tan delta, reflecting increased stiffness. A significant outcome is the thermal expansion behavior, where BJKKJBE composites exhibited the highest shrinkage (0.3%), while the KBJJBKE reinforcement, with kenaf as a skin layer, recorded the highest coefficient of thermal expansion (257 ppm °C ^−1 ). These findings present new opportunities for optimizing fiber-reinforced epoxy composites in applications requiring tailored thermal and thermo-mechanical performance, contributing to advancements in sustainable materials design for engineering applications.